Long past dues - Butcher, James J. (Butcher, James J. Unorthodox Chronicles, 2023)
"Grimsby, the newest Auditor in the magical Department of Unorthodox Affairs, finds himself in hot water when he intercepts a friend's case in this fast-paced and thrilling urban fantasy. Against all odds, Grimshaw Griswald Grimsby has become an Auditor, enforcing laws about magic for Boston's Department of Unorthodox Affairs. But Grimsby soon realizes the daily grind of his job is far removed from the glamour he imagined. Overlooked for every exciting case, Grimsby tires of being told to handle mundane magical troubles, and appropriates a case file intended for a friend. Alongside Leslie Mayflower, the temporarily unretired Huntsman, Grimsby aims to crack the case and discover the origin of a strange, unfinished ritual-one that seems to imitate the handiwork of a foe Mayflower put down twenty years ago. Together, they'll have to deal with escaped werewolves, a cursed artifact, and a perilous journey to the mysterious subterranean city below Boston, all to uncover the shocking truth. At any cost, Grimsby must stop this ritual from finally being completed. Yet the cost may be paid not by himself but by his friends. . . "--